TIME ANALYSIS WITH CRITICAL PATH METHOD: (Case Study on Jakarta Sewerage Development Project Zone 1, Package 2: Sewer Construction in Area 1-1) - Hartawan, Ade Sholeh; Witjaksana, Budi; Wulandari, Esti (Transpublika Publisher, 2024)
Preparatory work in a construction project generally includes the fulfillment of work facilities, field investigations, and licensing, and is typically non-structural. The implementation of the Jakarta Sewerage Development Project Zone 1, Package 2: Construction of Sewers in Area 1-1, which is currently still in the preparatory work stage, is experiencing significant issues. Specifically, the project is facing a very complex licensing process, resulting in minimal work progress. This is due to the project planning phase not adequately considering the timeframe required for obtaining an implementation permit. Therefore, this paper analyzes the project timeline to identify project performance during the preparation period before the main project work implementation stage. In this study, the Critical Path Method (CPM) scheduling method was applied to the project to determine the activities on the critical path, utilizing the Microsoft Project application. The analysis identified that the activities on this critical path include Document Submission Work, Shaft Location C-8.1 Work, 8-span Pipe Jacking Work, Diversion Chamber Work, and Contract Closing. The analysis of the relationship between the licensing process and the critical path of the Master Schedule, as determined by the CPM method, revealed a delay in the start time of Shaft work from the planned June 3, 2024, to June 21, 2024, representing a 17-day delay from the original plan.